The economic burden of musculoskeletal disorders on the Italian social security pension system estimated by a Monte Carlo simulation - S. Russo; T. T. Mariani; R. Migliorini; A. Marcellusi; F. S. Mennini (PAGEPress Publications, 2015)
The aim of the study is to estimate the pension costs incurred for patients with musculoskeletal disorders (MDs) and specifi cally with rheumatoid arthritis (RA) and ankylosing spondylitis (AS) in Italy between 2009 and 2012. We analyzed the database of the Italian National Social Security Institute (Istituto Nazionale Previdenza Sociale i.e. INPS) to estimate the total costs of three types of social security benefi ts granted to patients with MDs, RA and AS: disability benefi ts (for people with reduced working ability), disability pensions (for people who cannot qualify as workers) and incapacity pensions (for people without working ability). We developed a probabilistic model with a Monte Carlo simulation to estimate the total costs for each type of benefi t associated with MDs, RA and AS. We also estimated the productivity loss resulting from RA in 2013. From 2009 to 2012 about 393 thousand treatments were paid for a total of approximately €2.7 billion. The annual number of treatments was on average 98 thousand and cost in total €674 million per year. In particular, the total pension burden was about €99 million for RA and €26 million for AS. The productivity loss for AR in 2013 was equal to €707,425,191 due to 9,174,221 working days lost. Our study is the fi rst to estimate the burden of social security pensions for MDs based on data of both approved claims and benefi ts paid by the national security system. From 2009 to 2012, in Italy, the highest indirect costs were associated with disability pensions (54% of the total indirect cost), followed by disability benefi ts (44.1% of cost) and incapacity pensions (1.8% of cost). In conclusion, MDs are chronic and highly debilitating diseases with a strong female predominance and very signifi cant economic and social costs that are set to increase due to the aging of the population.